From milk by-products to milk ingredients : upgrading the cycle - Boer, Ruud de (Chichester, West Sussex : Wiley Blackwell, 2014)
This book mirrors the process of extracting ingredients from milk, beginning with the basic concepts and following through the processes until finally arriving at the consumer products that constitute the end uses of ingredients from milk. It begins by introducing the notion of ingredients from milk, with reference to the value of these ingredients, and the environmental and economic drive to use as many constituents as possible. It then looks at specific ingredients from milk (fats, proteins, serum), and shows how these form an expanding range. Protection of knowledge and patents are then addresses, and in particular how these are used in the industry to protect new products and processes. The recycling and reuse of raw materials from milk is then covered, with reference to cheese and its ingredients. The book then looks at various'outside restraints' on the process, such as safety requirements, sustainability drives, and the need for ingredients from milk to appeal to specialist groups (organic, kosher, halal). Vital separation technologies such as precipitation, chromatography, centrifugation, crystallization and membrane processes are then covered. Finally, the end uses of ingredients from milk in an array of different products and sectors are examined, including uses in the feed industry and pharmaceuticals as well as food industry applications.--COVER.
Ingredients -- Milk specifics -- Patents -- Reuse -- Outside constraints -- Vital membrane processes -- End users -- Information sheets.
Includes bibliographical references and index.
Keywords: Milk; Dairy products